2022
DOI: 10.1371/journal.pone.0262311
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex serological assay for the characterization of IgG immune response to SARS-CoV-2

Abstract: In the fight against SARS-COV-2, the development of serological assays based on different antigenic domains represent a versatile tool to get a comprehensive picture of the immune response or differentiate infection from vaccination beyond simple diagnosis. Here we use a combination of the Nucleoprotein (NP), the Spike 1 (S1) and Spike 2 (S2) subunits, and the receptor binding domain (RBD) and N-terminal domain (NTD) of the Spike antigens from the CoViDiag® multiplex IgG assay, to follow the immune response to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In contrast to monoplex assays such as ELISA, multiplex serological assays can simultaneously measure antibodies to multiple antigens, allowing for more epidemiological information to be obtained from a single test. It has been demonstrated that multiplex assays can have higher accuracy than monoplex assays [ 11 , 12 ]; can distinguish vaccinated from naturally infected individuals [ 13 ]; can provide estimates of the time since previous infection [ 3 ]; and can simultaneously measure immunity to seasonal coronaviruses [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to monoplex assays such as ELISA, multiplex serological assays can simultaneously measure antibodies to multiple antigens, allowing for more epidemiological information to be obtained from a single test. It has been demonstrated that multiplex assays can have higher accuracy than monoplex assays [ 11 , 12 ]; can distinguish vaccinated from naturally infected individuals [ 13 ]; can provide estimates of the time since previous infection [ 3 ]; and can simultaneously measure immunity to seasonal coronaviruses [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the research of Grossberg et al ( Grossberg et al, 2021 ) showed that the antibody levels of S1-RBD IgA, NP IgG, and S2 IgA can be used to identify severe, mild, and asymptomatic groups of COVID-19 patients. Considering increasing vaccination rates, combined detection of anti-NP and anti-Spike antibodies can also be used to differentiate the immune response from viral infection and accurately assess immunity ( Brochot et al, 2022 ). Compared with flow cytometry, the assay based on Pi-mqPCR can be combined with nucleic acid amplification tests and is more suitable for clinical serological diagnosis.…”
Section: Discussionmentioning
confidence: 99%